A Legislation-Based Database for COVID-19 Non-Pharmaceutical Interventions - Alexandros Kyriakidis; Nikolaos Zahariadis; Ioannis Papadopoulos (International Review of Public Policy)
In response to the COVID-19 pandemic, governments around the world imposed a wide variety of Non-Pharmaceutical Interventions (NPIs) in the form of restrictions of various aspects of social life, hoping to curb the spread of the SARS-CoV-2 virus. However, measures such as restrictions on public gatherings, the closure of schools, or the mandatory use of masks, raised several concerns in terms of both their necessity and effectiveness. The Observatory of Government Restrictive Measures for the COVID-19 pandemic (GovRM-COVID19), which began in November 2020 within the Center for Research on Democracy and Law of the University of Macedonia (Greece), has developed a database tracking all legislative measures imposing restrictions across different countries. The use of legislation as the main source of information with a daily frequency, as well as consideration of sub-federal entities in non-unitary (federal, devolved, etc.) states, provide one of the most accurate accounts of such restrictions. The end result provides researchers with accurate data on how various governments around the world have restricted individual rights and freedoms as a result of, and during, the COVID-19 pandemic, offering an opportunity for comparative research across different countries and policy strategies.